Antagonistic Activity of Endophytic Fungi from Dayak Onions’ Flower (Eleutherine bulbosa (Mill.) Urb.) Against Fusarium sp. Infecting Chili Plant - Aziza, Noor Laili; Sari, Noorkomala; Irsalina, Sofiya (Jurnal Fitopatologi Indonesia, 2022)
Antagonistic Activity of Endophytic Fungi from Dayak Onions’ Flower (Eleutherine bulbosa (Mill.) Urb.) Against Fusarium sp. Infecting Chili Plant Wilt disease caused by Fusarium spp. is an important problem in chili cultivation. Meanwhile, use of biological agents such as endophytic fungi from medicinal plants have the potential to control plant diseases. Dayak onions are medicinal plants that known to have antibacterial, anti-fungal, anti-inflammatory, and antioxidant properties. Therefore, a study was conducted to determine the antagonistic activity of endophytic fungi isolated from Dayak onion flowers against Fusarium spp. A total of seventeen isolates of endophytic fungi were obtained from the flower of Dayak onion flowers, namely EnA, EnB, EnC, EnD, EnE, EnF, EnG, EnH, EnI, EnJ, EnK, EnL, EnM, EnN, EnO, EnP, and EnQ. Five of the seventeen isolates, i.e. EnA, EnF, EnI, EnJ, and EnK were further examined in antagonistic test against Fusarium spp. using dual culture method. Inhibition of colony growth of Fusarium spp. caused by isolates EnA, EnF, EnI, EnJ, and EnK were 67.6%, 53.15%, 77.25%, 70.42% and 67.1%, respectively.